Cost-effectiveness analysis of short versus long cephalomedullary nails for treatment of stable intertrochanteric femoral fractures: a theoretical cohort study. Issue 6 (21st November 2021) - Fuller, Carson C.; Kweon, Christopher; Baker, Timothy; Reese, Carlie; Lack, William D.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Cephalomedullary nails are the current preferred method of fixation for the treatment of intertrochanteric fractures. Both short and long nails are currently used, and physician and institutional preferences are highly variable. Methods: Literature on intertrochanteric fracture types as categorized by the AO/Orthopaedic Trauma Association (AO/OTA) 31-A1, A2, and A3, was reviewed to determine failure rates requiring reoperation and health utility values. A decision-tree baseline followed by a Monte Carlo simulation was used to determine cost-effectiveness of each nail length at an incremental cost-effectiveness ratio threshold of 100, 000 per quality-adjusted life-year. Procedural costs were derived from Medicare reimbursement rates and incremental costs of long nails were calculated using primary literature. Results: The model demonstrates short nails to be the more cost-effective implant. At the mean incremental long nail cost of 1, 950 the short nail had an incremental cost-effectiveness ratio greater than 100, 000/quality-adjusted life-year when the secondary fracture rate of short nails was at the mean value of 1.5%. At a short nail fracture rate greater than 2.4%, long nails were more cost-effective. In our theoretical cohort, a probabilistic sensitivity analysis demonstrated the short nail to be the cost-effective method 70% of the time at a willingness to pay of 100, 000. Conclusions: Given the current reported failure ranges, short nails are the more cost-effective approach for the treatment of stable intertrochanteric femoral fractures. These conclusions are highly sensitive to the secondary fracture rate, which could confound our analysis because of limitations in length and quality of follow-up in the available primary literature. Level of Evidence: Level III.